2015
DOI: 10.1186/1750-1326-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Aβ reduction in BACE1 heterozygous null 5XFAD mice is associated with transgenic APP level

Abstract: BackgroundThe β-secretase, BACE1, cleaves APP to initiate generation of the β-amyloid peptide, Aβ, that comprises amyloid plaques in Alzheimer’s disease (AD). Reducing BACE1 activity is an attractive therapeutic approach to AD, but complete inhibition of BACE1 could have mechanism-based side-effects as BACE1−/− mice show deficits in axon guidance, myelination, memory, and other neurological processes. Since BACE1+/− mice appear normal there is interest in determining whether 50% reduction in BACE1 is potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
129
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 44 publications
24
129
3
Order By: Relevance
“…27, 2017; significant main effect of strain was observed [F(22,153) = 2.1, p = 0.01], indicating that genetic background significantly modified the Aβ42 levels across the panel. No main effect of sex was observed [F(1, 153) = 1.4, p = 0.25], in contrast to a previous report using a single genetic background suggesting the 5XFAD model preferentially affect females (Sadleir et al, 2015).…”
Section: Ad-bxd Panel Exhibits Heritable Variation In Amyloid Patholocontrasting
confidence: 91%
“…27, 2017; significant main effect of strain was observed [F(22,153) = 2.1, p = 0.01], indicating that genetic background significantly modified the Aβ42 levels across the panel. No main effect of sex was observed [F(1, 153) = 1.4, p = 0.25], in contrast to a previous report using a single genetic background suggesting the 5XFAD model preferentially affect females (Sadleir et al, 2015).…”
Section: Ad-bxd Panel Exhibits Heritable Variation In Amyloid Patholocontrasting
confidence: 91%
“…Our recent data demonstrated that synaptic store-operated calcium entry (nSOC) plays an important role in control of stability of hippocampal (Popugaeva et al, 2015; Sun et al, 2014; Zhang et al, 2015) and striatal (Wu et al, 2016) synaptic spines. In HD, mHtt binds to and sensitizes InsP 3 R1 to basal levels of InsP 3 (Tang et al, 2003), increasing Ca 2+ leakage from the ER (Tang et al, 2005; Tang et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Because the kinetics of plaque deposition have been reported to be gender-dependent [1316], we selected cohorts containing only a single gender within each line; with this criterion, we had available tissue from female 5XFAD mice and from male mice of the other three lines. We elected to proceed with this study with the tissue currently available, as gender is only one among several factors that can influence plaque deposition or AβPP metabolism, including background strain [17], housing conditions [18, 19] and even maternal diet [20] or activity [21].…”
Section: Introductionmentioning
confidence: 99%